Numerical investigation of oblique detonation structure in hydrogen-oxygen mixtures with Ar dilution. (15th September 2019) - Tian, Cheng; Teng, Honghui; Ng, Hoi Dick
Abstract: Two combustible mixtures, H2 -O2 -Ar and H2 -O2 -N2, are widely used in detonation research, but only the latter has been employed in oblique detonation wave (ODW) studies. In this study, ODWs in H2 -O2 -Ar are simulated to investigate their structural characteristics using reactive Euler equations with a detailed chemistry model. Similar to ODWs in H2 -O2 -N2 mixtures, two observed structures are dependent on incident Mach numbers. However, in mixtures of 2H2 + O2 + 7Ar, the structures are sensitive to inflow static pressure P0, different from the structures in H2 -O2 -N2 mixtures. Based on flow field analysis, the ratio of induction and heat release zone lengths RL is proposed to model the difference induced by dilution gas. Generally, RL is large in N2 diluted mixtures but small in Ar diluted mixtures. Low RL indicates that induction is comparable with the heat release zone and easily changed, resulting in pressure-sensitive structures. When the dilution gas changes gradually from N2 to Ar, the ratio RL increases slowly at first and then declines rapidly to approach a constant. The variation rule of RL is analyzed and compared with results from calculations of a constant volume explosion, demonstrating how different dilution gases influence ODW structures.